"Being a Therapist Doesn't Exclude You From Real Life": Family Therapists' Beliefs and Barriers to Political Action. (2nd August 2017) - Jordan, Lorien S.; Seponski, Desiree M.
Abstract : A crucial and overlooked facet of social justice in family therapy is political and policy advocacy. Family therapists have unique insight into how social policies and political discourse shapes clients' lives and the life of our profession. Such knowledge can inform policymakers and political debate, yet few family therapists are trained to engage in political action. In this randomized, national survey of licensed family therapists' ( N = 174), we explore beliefs about and barriers to engagement in political and policy processes. The findings suggest that there are significant barriers and uncertainties surrounding family therapists' engagement, including time, feelings of efficacy, and interest. Given these barriers we discuss practical suggestions for clinicians and family therapy training programs.